2014
DOI: 10.1017/s0007114514000178
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin (vitamin B2) and oxidative stress: a review

Abstract: Oxidative stress is involved in the development of many chronic diseases. One of the main factors involved in oxidative stress reduction is increased antioxidant potential. Some nutrients such as vitamin C, vitamin E and carotenoids are known to act as antioxidants; however, riboflavin is one of the neglected antioxidant nutrients that may have an antioxidant action independently or as a component of the glutathione redox cycle. Herein, studies that have examined the antioxidant properties of riboflavin and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
232
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(243 citation statements)
references
References 53 publications
5
232
0
6
Order By: Relevance
“…Furthermore, we observed that ectopic expression of GPR172B inhibited senescence. This effect appears to be reasonable because GPR172B is a membrane transporter for riboflavin (also known as vitamin B2) that acts as a coenzyme for redox enzymes essential for cellular homeostasis4546. This result raises the possibility that p53 also drives a negative feedback loop that limits activation of senescence-inducing signalling pathways to prevent accidental induction of senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we observed that ectopic expression of GPR172B inhibited senescence. This effect appears to be reasonable because GPR172B is a membrane transporter for riboflavin (also known as vitamin B2) that acts as a coenzyme for redox enzymes essential for cellular homeostasis4546. This result raises the possibility that p53 also drives a negative feedback loop that limits activation of senescence-inducing signalling pathways to prevent accidental induction of senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Ashoori and Saedisomeolia [27] explained in their study "Riboflavin (vitamin B2) and oxidative stress: A review" the confirmation of antioxidant nature of riboflavin and indicated that this vitamin can protect the body against oxidative stress, especially lipid peroxidation and reperfusion oxidative injury. The mechanisms by which riboflavin protects the body against oxidative stress may be attributed to the glutathione redox cycle and also to other possible mechanisms such as the conversion of reduced riboflavin to the oxidised form.…”
Section: Vitamin B 2 (Riboflavin)mentioning
confidence: 99%
“…It has been reported in clinical studies that riboflavin may reduce the pain in humans [21,22], although recent papers did not support the prophylactic effects of riboflavin [23,24]. More recent studies have suggested that at least some subtypes of migraines may be related to a mitochondria defect.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have suggested that at least some subtypes of migraines may be related to a mitochondria defect. Different types of evidence support a relationship between mitochondria and migraines [21,22]. Riboflavin works as a coenzyme in the mitochondrial electron transport chain [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation